Contribution of Hand Eye Coordination and Arm Muscle Strength to Volleyball Serving Ability - Nugraha, Jaka Setia; Handayani, Widya; Lestari, Hikmah (PPSDP International Journal of Education, 2024)
The aim of the research is to find out whether there is a contribution between the eyes and arms and arm muscle strength on the ability of the upper body in the sport of volleyball among students at SMA 08 Oku. Correlation research method with quantitative enhancement. The samples are X.1 and Data collection techniques are tests and documentation. The data analysis techniques are normality test, multiple linear correlation, T test and F test. The results of the correlation research for X1 and Y produced a figure of 0.892, while X2 and Y produced a figure of 0.892. For the F test, Fcount (86.470) > Ftable (3.555) and the significant p-value < 0.05, namely 0.000. So it is concluded that Ho is rejected, this means that push-ups and wrist flexibility affect the volleyball serve.